1996
DOI: 10.1097/00004714-199602000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Acute Tolerance to Subjective but not Cardiovascular Effects of d-Amphetamine in Normal, Healthy Men

Abstract: This is a descriptive report on the relationship between the pharmacokinetics and pharmacodynamics of d-amphetamine in healthy, normal volunteers. Six men, aged 22 to 31, attended two experimental sessions during which they received single oral doses of 20 mg of d-amphetamine. Plasma levels of drug and measures of drug effect were collected predrug and at regular intervals for 24 hours after drug administration. Plasma drug levels peaked at 4 hours and remained at detectable levels for 24 hours after drug admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
34
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 16 publications
8
34
0
1
Order By: Relevance
“…A related point is that 24 hours following methamphetamine administration (primarily the 50-mg dose), physiological measures remained significantly elevated and this might have potential implications for toxicity. For example, de Wit and colleagues showed that tolerance develops more rapidly to oral amphetamine-related subjective effects relative to physiological effects (Brauer et al 1996). Thus, in the natural environment, some users may take repeated methamphetamine doses in order to achieve a certain level of intoxication, which might increase the likelihood of physiological harm (e.g., cardiotoxicity).…”
Section: Discussionmentioning
confidence: 99%
“…A related point is that 24 hours following methamphetamine administration (primarily the 50-mg dose), physiological measures remained significantly elevated and this might have potential implications for toxicity. For example, de Wit and colleagues showed that tolerance develops more rapidly to oral amphetamine-related subjective effects relative to physiological effects (Brauer et al 1996). Thus, in the natural environment, some users may take repeated methamphetamine doses in order to achieve a certain level of intoxication, which might increase the likelihood of physiological harm (e.g., cardiotoxicity).…”
Section: Discussionmentioning
confidence: 99%
“…For example, amphetamine is known to have vasoconstrictive effects, which can result in alterations of blood flow (Simpson 1976;Angrist et al 1987;Brauer et al 1996). Although it seems unlikely, amphetamine may have directly affected blood flow only in the specific brain areas where changes in the activation pattern were observed.…”
Section: Discussionmentioning
confidence: 99%
“…S began the Lexical Salience Task 90 min after dosing, at which time the subjective-behavioral effects of oral AMPH are maximal (Brauer et al, 1996). Upon completion of the task (3-5 min), S completed the modified visual analog scales and the MAACL.…”
Section: Methodsmentioning
confidence: 99%